Isomaltulose and normal energy‐yielding metabolism: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006. (20th October 2021) - ,; Turck, Dominique; Bohn, Torsten; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; et al.
Abstract: Following an application from BENEO GmbH submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Germany, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to isomaltulose and normal energy‐yielding metabolism. The scope of the application was proposed to fall under a health claim based on newly developed scientific evidence. The food proposed by the applicant as the subject of the health claim is isomaltulose. The Panel considers that isomaltulose is sufficiently characterised. The claimed effect proposed by the applicant is 'normal energy‐yielding metabolism'. The Panel considers that contribution to normal energy‐yielding metabolism is a beneficial physiological effect. A number of human studies applying indirect calorimetry measurements or stable isotope methodologies have shown the postprandial metabolic utilisation of isomaltulose as energy source. However, all energy‐containing macronutrients (i.e. carbohydrates, proteins, and lipids) supply the body with energy and this property is not specific to isomaltulose. The Panel concludes that a cause and effect relationship has been established between the intake of isomaltulose and contribution to energy‐yielding metabolism. The following wording reflects the scientific evidence: 'isomaltulose contributes to normal energy‐yielding metabolism'. Since the contribution to energy‐yielding metabolism is not specific to isomaltulose but applies to all energy containing macronutrients (i.e. carbohydrates, proteins, and lipids) that supply the body with metabolisable energy and any amount would contribute to the claimed effect, the Panel cannot set conditions of use for this claim. The applicant proposes that isomaltulose should replace other sugars in foods and/or beverages. The target population is the general population.